ANALISIS KOMPARATIF KINERJA KEUANGAN (STUDI PADA CV.NIAGARA SWALAYAN DAN CV. KANJI NIAGA SEJATI BUKITTINGGI) - Najlani Syamsuddin; Mariaty Ibrahim (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine and analyze the level of financial performance of the ratio of liquidity, solvency, profitability and activity. CV. Niagara Supermarkets Bukittinggi and CV. Kanji Niaga Sejati Bukittinggi during the period 2014-2018.This study uses secondary data in the form of data obtained by the author through secondary data in the form of information and information in the form of financial reports obtained from agencies or companies related to this research which are needed by researchers for analysis of liquidity, solvency, and activities.The results of the analysis show that the analysis of the financial statements of CV. Niagara Supermarkets Bukittinggi for the period 2014-2018 based on Liquidity, Solvency, Profitability and Activity Ratios are: 1). Liquidity ratio analysis, the current ratio is in a